Analysis of internal determinants of profitability of regional development banks - lia Asria (Indonesia Auditing Research Journal, 2021)
In creating a good economic system has to be supported with a solid, healthy and profitable banking system. Within the banking system, profitability is an important influence on the performance of a bank because it describes the effectiveness level of funding management that is collected from people. One step done by the government and people in improving financial stability and banking was first identified the internal determination factors that can be used as a guide in banking performance improvement so that the result achieved the target. Regional Development Bank is the research object chosen for this research. This research will give some answers to what internal factors significantly influence the profitability of Regional Development Banks. The collected data was the financial report quarterly from 23 BPDs that were taken as samples of the research. While the method used to analyze the data was the linear regression method with F and t tests. From the analysis of the results of the method it can be concluded that the management expenses, liquidity and capital factors have a significant influence on banking profitability both simultaneously and partially.